Pengaruh Komunikasi dan Motivasi terhadap Kinerja Karyawan Pada PT Mandiri Sejahtera Abadi - Aji Purnomo; Sulistiyo Seti Utami (ITB Ahmad Dahlan Jakarta, 2020)
The purpose of this study was to analyze how much influence of communication on performance, motivation on performance, the effect of communication and motivation simultaneously on employee performance at PT. Mandiri Sejahtera Abadi. This research design uses quantitative descriptive methods and data collection techniques for library research (Library Research) and field research (Field Research). The data analysis technique used in this research is using data instrument test analysis, multiple linear regression test, correlation test, determination test, t-test and f test by testing communication variables, motivation and performance. The results of this study indicate that with multiple linear analysis, a constant value of 2.960 is obtained, which means that if communication and motivation do not change or are almost close to 0, then the Work Performance (Y) created is 2.960 and these results do not change. From the results of the t-test for the communication variable on employee performance, the value of t-value (6.134)> t-table (2.004) was obtained. Significant test results show that the correlation value of the communication variable is 0.000. Meanwhile, the motivation variable is 0.000. It means that the influence of these variables is super strong. The coefficient of determination results is 0.827, so it can be concluded that the communication and motivation variable has an effect of 83% on employee performance. More elaboration oh those finding is presented in this paper.